CATHODIC BEHAVIOUR of ANODIZED TITANIUM IN SIMULATED PHYSIOLOGICAL CONDITIONS - Pelaez Abellan, E. (2011)
In the present work, anodic oxide films on titanium specimens were formed in physiological solution under potentiostatic condition. The immediate- to short-term changes in the oxide film were studied by open-circuit potential measurements and cyclic voltammetry. The results show that the intensity of the cathodic current peak related to oxygen reduction at around -0.7 Vsce, decreased and disappeared after 30 minutes of finishing the anodic oxidation. For titanium without anodization (non-coated titanium), the cyclic voltammograms show an anodic current in the range that begins at -0.9 Vsce and continues to more positive potentials (vs SCE), related to the hydrogen oxidation reaction. For anodically polarized titanium (coated titanium), in the anodic direction of the cyclic voltammograms an anodic current in the range that begins at -0.9 Vsce and continues to more positive potentials (vs SCE) was observed. In this case, the oxidation process is related to previous cathodic processes: the hydrogen formation and the cathodic transformation of titanium oxides before the oxygen reduction potential region.